Análisis componencial de las lexías de las coplas del carnaval de Guaranda - Soto Ramírez, Corayma Alejandra (2025)
The componential analysis of the lexias of the coplas of the carnival of Guaranda aims to analyze the lexias of the coplas of the city of the eternal carnivals, through the componential study, with the guidance of the research of Laura Hidalgo Alzamora, who contributes with a collection of popular literature facilitating the study of the lexias. The work was carried out with a qualitative approach, given that the area of knowledge is framed in the educational sciences and focuses on interpretation. Regarding the modality or research design, it was characterized as non-experimental because no variable was controlled. In terms of level and scope, the research is diagnostic, exploratory and descriptive. The sample is non-probabilistic due to the choice of 20 lexias selected from the book “Coplas del carnaval de Guaranda” by Laura Hidalgo, with the help of diagrams and tables for the componential analysis and lexical field. After concluding the analysis, it was found that the lexias are mostly present in the couplets that belong to the themes of humor, jokes, gallantry, mischief, food, love, marriage and women. On the other hand, in the semantic fields they broadened the understanding based on the organization and structure of the lexies to understand and differentiate the meaning of the terms within the connotative and denotative context. In addition, it was determined that the coplas of the carnival of Guaranda are part of the identity and tradition of the city.